2019
DOI: 10.1002/da.22962
|View full text |Cite
|
Sign up to set email alerts
|

Impaired neural habituation to neutral faces in families genetically enriched for social anxiety disorder

Abstract: BackgroundSocial anxiety disorder (SAD) is an incapacitating disorder running in families. Previous work associated social fearfulness with a failure to habituate, but the habituation response to neutral faces has, as of yet, not been investigated in patients with SAD and their family members concurrently. Here, we examined whether impaired habituation to neutral faces is a putative neurobiological endophenotype of SAD by using data from the multiplex and multigenerational Leiden Family Lab study on SAD.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Second, we investigated responses to neutral faces. Data revealed that impaired neural habituation in the hippocampus met the two endophenotype criteria of interest 145 ; in addition, amygdala engagement in response to conditioned faces with a social-evaluative meaning qualified as a neurobiological candidate endophenotype of social anxiety 146,147 . Although future studies are required to examine the stability of these candidate endophenotypes over time (endophenotype criterion 2) and to discover genetic variants underlying the abovementioned candidate endophenotypes, these promising findings offer a starting point for follow-up studies on the genetic susceptibility to SAD.…”
Section: Endophenotype Research On Social Anxiety Disordermentioning
confidence: 98%
“…Second, we investigated responses to neutral faces. Data revealed that impaired neural habituation in the hippocampus met the two endophenotype criteria of interest 145 ; in addition, amygdala engagement in response to conditioned faces with a social-evaluative meaning qualified as a neurobiological candidate endophenotype of social anxiety 146,147 . Although future studies are required to examine the stability of these candidate endophenotypes over time (endophenotype criterion 2) and to discover genetic variants underlying the abovementioned candidate endophenotypes, these promising findings offer a starting point for follow-up studies on the genetic susceptibility to SAD.…”
Section: Endophenotype Research On Social Anxiety Disordermentioning
confidence: 98%
“…The Leiden Family Lab study on Social Anxiety Disorder (LFLSAD) is to our knowledge the first comprehensive two-generation family neuroimaging study on SAD and has been designed specifically to examine the heritability and first part of the co-segregation criteria of candidate endophenotypes of SAD ( Bas-Hoogendam et al, 2018a ). Previous results of this study suggest that several characteristics of brain structure and function, like cortical and subcortical GM characteristics, increased and prolonged amygdala activation, and increased brain activity whilst processing unintentional social norm violations, could be endophenotypes of SAD ( Bas-Hoogendam et al, 2018b , Bas-Hoogendam et al, 2019b , Bas-Hoogendam et al, 2019c , Bas-Hoogendam et al, 2020b , Bas‐Hoogendam et al, 2019a ). However, it still remains to be elucidated whether characteristics of WM microstructure could be candidate endophenotypes of SAD.…”
Section: Introductionmentioning
confidence: 65%
“…Participants with (sub)clinical SAD reported significantly higher levels of social anxiety (self-reported social anxiety symptoms (z-SA) and FNE), depressive symptoms and trait anxiety compared to their non-SAD relatives but did not differ with respect to gender-distribution, generation, age or IQ. For a more elaborate description of this sample, including diagnostic information and details on quality checking and data availability, we refer to the Supplemental section and previous publications on the LFLSAD in general ( Bas-Hoogendam et al, 2018a ) and the MRI sample in particular ( Bas-Hoogendam et al, 2018b , Bas-Hoogendam et al, 2019b , Bas-Hoogendam et al, 2020b , Bas‐Hoogendam et al, 2019a ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations